Solving the problems of forecasting long-term strength under plane stress - Регульський, М.М.; Борозенець, Г.М.; Касперська, В.В. (Proceedings of National Aviation University (archive), 2007)
This work is carried out in view of development of analytical approach to the time to fracture calculation of thin-walled structural components under long-term biaxial loading. The approach is based on the equivalent stresses concept. The calculation of the time to fracture of thin-walled tubular specimens under internal pressure, internal pressure with tension, pure torsion, torsion with tension is presented. A satisfactory agreement of the calculations with experimental data is obtained. The assessment of the agreement is performed by means of regression analysis and drawing of the confidence boundaries.